Intercostal Nerve Block and Neurolysis for Intractable Cancer Pain. (2nd April 2016) - Matchett, Gerald
ABSTRACT: Management of intractable cancer-associated chest wall pain is difficult once patients have reached dose-limiting side effects of opioids and coanalgesic medications. This case series describes 11 patients with intractable cancer-associated chest wall pain who were treated with a diagnostic intercostal nerve block. Six patients subsequently received chemical neurolysis with phenol using the same approach. No serious adverse events were observed. Radiopaque contrast dye spread into the paravertebral space in all 11 patients, and in 1 patient contrast dye spread into the epidural space. Seven of 11 patients experienced pain relief from the diagnostic blockade. Four of six patients experienced pain relief from the neurolytic blockade. The principal reportable finding from this case series is the observation that contrast dye spread liberally from the intercostal space into other anatomic spaces, even though very small volumes of injectate (less than 5 mL) were used. Definitive evidence of safety and efficacy of intercostal nerve block and neurolysis for cancer pain will require a prospective randomized clinical trial.